The Emerald international handbook of feminist perspectives on women's acts of violence - Banwell, Stacy; Black, Lynsey; Cecil, Dawn K.; Djamba, Yanyi K.; Kimuna, Sitawa R.; Milne, Emma; Seal, Lizzie; Tenkorang, Eric Y. (Emerald Publishing Limited, 2023)
Violence by women is frequently sensationalised, abetting misogynistic tropes that characterise violent women as evil, unnatural and masculine. Favouring more complex analyses of this behaviour, The Emerald International Handbook of Feminist Perspectives on Womens Acts of Violence highlights and challenges normative accounts of womens violence and offers new multidimensional conceptualisations of these acts, furthering understanding of this topic from a feminist perspective. Responding to a growing research interest, contributors present a comprehensive introduction to a wide range of international and interdisciplinary scholarship on different aspects of womens violence. Drawing on both empirical and secondary data, chapters incorporate familiar themes of intimate violence, homicide, terrorism and combat as well as wider content such as womens involvement in violent nationalist movements and their role in perpetrating obstetric harms. The only publication of its kind in terms of its scope, interdisciplinarity and feminist perspective, The Emerald International Handbook of Feminist Perspectives on Womens Acts of Violence breaks fresh ground by unveiling how violence is understood and enabling new links and connections to be made across previously disparate areas.